KERAGAMAN SEKTOR INFORMAL DALAM HUBUNGANNYA DENGAN MIGRASI MASUK DAN REMITAN (Kasus di Negeri Batu Merah, Kota Ambon) - Felecia P Ada (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2014)
This study aims to (1) determine the diversity of the informal sector in the Negeri Batu Merah, Ambon and (2)determine the possibility of remittance practices, by the Javanese migrants.The method used was a descriptive qualitative approach. The data obtained were the primary and secondarydata as well as documentation collected through in-depth interviews with 30 respondents. Analysis of the data wasconducted by using model of Spradley, in which the focus of the observations were made on three major componentsrespectively; space (place), actors and activities.The results showed that (1) the diversity of the informal sector includes a pedicab driver, an old iron buyersand peddlers (meatballs, cakes, herbs, chicken noodle, soto soup, Sarmento, vegetable peddlers, chocolate banana,chicken satay, fried snack and fried rice), and (2) there was 72 percent of migrants send remittances to their familiesin the area of origin regularly with the average of Rp 1,343,33.33 per month. The migrants come from various citiesin West Java, East Java and Central Java such as; Solo, Karanganyer, Demak, Wonogiri, Ngawi, Tegal, Sidoarjo,Sukoharjo, Sumedang, Lamongan, Bojonegoro, Trenggalek, Jombang and Kebumen.